2016
DOI: 10.1039/c6cc04233c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, aggregation-enhanced emission, polymorphism and piezochromism of TPE-cored foldamers with through-space conjugation

Abstract: A series of new folded tetraphenylethene derivatives with different substituents are stereoselectively synthesized, which exhibit interesting through-space conjugation, aggregation-enhanced emission, polymorphism and piezochromism properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
(5 reference statements)
3
15
0
Order By: Relevance
“…The archetypal foldamer, Z-o-BPTPE, has been confirmed by crystallographic analysis to be a cis-isomer. The specific phenyl rings, Φ 1 and Φ 2 , are stacked in a nearly parallel manner, with a plane overlap of about 50% and inter-ring distances of 3.147 and 3.166 Å (Figure 6), [55][56][57] indicating the existence of efficient electronic coupling between the stacked phenyl rings. Compared with the conventional [2.2]pCp, Z-o-BPTPE performs better in photoluminescence and charge transport.…”
Section: New Through-space Conjugated Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The archetypal foldamer, Z-o-BPTPE, has been confirmed by crystallographic analysis to be a cis-isomer. The specific phenyl rings, Φ 1 and Φ 2 , are stacked in a nearly parallel manner, with a plane overlap of about 50% and inter-ring distances of 3.147 and 3.166 Å (Figure 6), [55][56][57] indicating the existence of efficient electronic coupling between the stacked phenyl rings. Compared with the conventional [2.2]pCp, Z-o-BPTPE performs better in photoluminescence and charge transport.…”
Section: New Through-space Conjugated Systemmentioning
confidence: 99%
“…Moreover, by exploring other TPE-cored foldamers with different branched chains, we have concluded that the substituents with a different electronic nature and heterocycles can regulate the stacking geometry and optical properties, but show no apparent impact on the formation of a folded architecture. These foldamers exhibit an efficient through-space conjugation and aggregationenhanced emission (AEE) [55][56][57][58][60][61][62][63] property because of the increased molecular rigidity. In view of this observation, regulating the geometric and electronic structures of the foldamers to control the degree of through-space conjugation should be helpful for manipulating photophysical properties and potential functions.…”
Section: New Through-space Conjugated Systemmentioning
confidence: 99%
“…Accordingly,avariety of aromatic groups were introduced at the ortho position of benzophenone to construct as eries of (Z)-TPE derivatives. [80][81][82][83][84][85][86] The chemical structures of these compounds are showninFigure 17, along with their corresponding CCDC numbers. [98] The simplest( Z)-o-BPTPE served as the core of the Z derivatives.…”
Section: Stereoselective Synthesis Of Pure (Z)-/(e)-tpe Isomersmentioning
confidence: 99%
“…In previous work, we established a new class of hybrid conjugation system of tetraphenylethene (TPE)-cored foldamers, which employ TPE as a TBC core and fold a pair of aryl wings (fragments or chains) into a π-stacking TSC component. [46][47][48][49] Utilizing such a fantastic geometry, efficient luminescent materials, bipolar carrier transporting materials, 50 and multichannel single-molecular wires 51,52 have been successfully created. In addition, preliminary investigations on the structure-property correlation have been carried out.…”
Section: Introductionmentioning
confidence: 99%